Impacts of Human Activities and Environmental Changes on Spatial-Seasonal Variations of Metals in Surface Sediments of Zhanjiang Bay, China - Zhou, Fengxia; Xiong, Mengqi; Wang, Shuangling; Tian, Sheng; Jin, Guangzhe; Chen, Fajin; Chen, Chunqing; Lu, Xuan; Zhu, Qingmei; Meng, Yafei (Frontiers in Marine Science, 2022)
This study investigated the total concentrations and geochemical compositions of metals (Cd, Cr, Cu, Ni, Pb, Zn, Fe and Mn) in surface sediments of Zhanjiang Bay (ZJB) in spring and summer, to assess the contamination status, mobility and influencing factors of spatial-seasonal changes of these metals. The average total concentration for each studied metal in the surface sediments of ZJB was 0.173 μg/g for Cd, 58.25 μg/g for Cr, 17.11 μg/g for Cu, 16.89 μg/g for Ni, 28.70 μg/g for Pb, 67.91 μg/g for Zn, 30.18 mg/g for Fe, and 275.5 μg/g for Mn during the investigation period. Generally higher total concentrations of metals were found in the channel and coastal sediments of ZJB compared with those in the central ZJB, which may be probably resulted by the input of Suixi river, domestic sewage and industrial wastewater. The grain size compositions and TOC contents also had influences on the distributions of metals in ZJB. In the channel, total metals and reducible and bioavailable fractions of metals generally showed decreased concentrations in summer compared with those in spring, suggesting the release of metals from sediments. Organic matter degradation and Fe and Mn (hydr)oxides reduction processes may contribute much to this phenomenon. Relatively high proportions of Cd and Zn (average of 21.7% and 14.6%, respectively) were associated with the acid soluble fraction, indicating their high risk to the environment. The combined assessment results of enrichment factor, contaminated factor and the percentages of acid soluble fraction indicated that Cd and Zn in the surface sediments of ZJB were generally contaminated and they had medium to high risk to the environment. The average values of pollution load index in the channel, coastal and central ZJB were 1.28, 0.93 and 0.81, respectively, indicating the deterioration of surface sediments in the channel of ZJB. More attention should be paid on the metals in surface sediments of the channel of ZJB.